Eksplorasi (Electric Separating Sperm) ESS dalam Keberlanjutan Peningkatan Produksi dan Reproduksi Melalui Seleksi Sperma serta Penentuan Jenis Kelamin Ternak Kambing PPKDN Desa Sambirejo, Kecamatan Bangorejo, Banyuwangi - Amung Logam Saputro; Ratih Novita Praja; Wayan Ari wijaya; Shifa Salsabilla Praja; Wira Tirta Jaladara; Jihan Annisa; Dilla Chelsea Aziizahrani Santoso; Evelyn Zalfa Winni Kusuma; Arya Agung; Muhammad Ivan Maulana; Amalia Sofi Ramadanti; Annerda Yurika (LOSARI DIGITAL, 2026)
Bangorejo District, Banyuwangi Regency, East Java, has significant potential for goat farming development; however, it still faces challenges related to productivity and reproductive efficiency due to the limited adoption of modern reproductive technologies. This community service program aimed to improve farmers’ knowledge and skills through the implementation of Electric Separating Sperm (ESS) technology. The activities were conducted through counseling sessions, training, and demonstrations of ESS application involving 30 goat farmers in Sambirejo Village. The effectiveness of the program was evaluated using pre-test and post-test methods. The results showed an increase in the number of correct responses across all question indicators (P1–P15), with an average improvement of 1–2 participants per indicator, equivalent to approximately 3.3–6.7% of the total participants. This improvement indicates enhanced farmer understanding of sperm sexing technology and livestock reproductive management. The implementation of ESS provides a simpler reproductive technology alternative with potential applicability at the smallholder farmer level to support reproductive efficiency and sustainably improve goat productivity.